Effects of Fluoxetine Treatment on Striatal Dopamine Transporter Binding and Cerebrospinal Fluid Insulin-Like Growth Factor-1 in Children with Autism - Makkonen, I.; Kokki, H.; Kuikka, J.; Turpeinen, U.; Riikonen, R. (Neuropediatrics, 2011)
A positive effect of fluoxetine has been shown in some children with autism. The present study was undertaken to correlate striatal dopamine transporter (DAT) binding and cerebrospinal fluid insulin-like growth factor-1 (CSF-IGF-1) with clinical response in autistic children (n=13, age 5–16 years) after a 6-month fluoxetine treatment. Good clinical responders (n=6) had a decrease (p=0.031) in DAT binding as assessed using single-photon emission computed tomography with [123I]-nor-β-CIT, whereas poor responders had a trend to an increase. An increase in CSF-IGF-1 (p=0.003) was detected after the treatment period, but no correlation between the clinical response and CSF-IGF-1 was found. In conclusion, fluoxetine decreases DAT binding indicating alleviation of the hyperdopaminergic state and increases CSF-IGF-1 concentration, which may also have a neuroprotective effect against dopamine-induced neurotoxicity in autistic children.
Keywords: autism; dopamine transporter; fluoxetine; insulin-like growth factor-1